Epidemiological characteristics of chronic non-communicable diseases in Dongfang, China, 2021: a cross-sectional survey - Lan Chen; Chunmei Zhang; Chunyan Zhao; Liang Zheng; Xingyi Chen; Meixuan Song (BMJ Open)
Objectives The study aimed to understand the composition, epidemiological characteristics and disease burden of chronic non-communicable diseases and to evaluate the association between sociodemographic factors and chronic non-communicable diseases.Design A cross-sectional study.Setting and participants Medical records of 196 761 residents were collected from Dongfang disease surveillance system from January to December 2021.Primary outcome Prevalence and disability burden were recorded. Logistic regression was used to investigate the relationship between sociodemography factors and diseases.Results Cardiovascular diseases, chronic lower respiratory diseases and other upper respiratory tract diseases were the main chronic non-communicable diseases. In multivariable analysis, men were associated with increased risk of cardiovascular diseases (OR=1.210, 95% CI 1.162 to 1.261) and chronic lower respiratory diseases (OR=1.128, 95% CI 1.079 to 1.180). Older age was associated with increased risk of cardiovascular diseases (OR=83.952, 95% CI 58.954 to 119.550), whereas was associated with decreased risk of chronic lower respiratory diseases (OR=0.442, 95% CI 0.415 to 0.471) and other upper respiratory tract diseases (OR=0.450, 95% CI 0.411 to 0.493). The unemployed and poor household were associated with decreased risk of cardiovascular diseases (OR=0.463, 95% CI 0.412 to 0.521 and OR=0.390, 95% CI 0.342 to 0.444, respectively), whereas were associated with increased risk of chronic lower respiratory diseases (OR=12.219, 95% CI 6.343 to 23.539 and OR=10.954, 95% CI 5.666 to 21.177, respectively) and other upper respiratory tract diseases (OR=2.246, 95% CI 1.719 to 2.936 and OR=3.035, 95% CI 2.308 to 3.991, respectively). Gender and age moderated the association between personnel category and major diseases.Conclusions The spectrum and epidemiological characteristics of chronic diseases observed in Dongfang is good evidence for developing prevention guides and health policies for region.